Oral Health and Quality of Life Among Elderly in Thailand - Samnieng, Patcharaphol; Lekatana, Hathairat (UI Scholars Hub, 2016)
Oral health contributes physically and psychologically to quality of life. Objective: To investigate the relationship of oral health status with oral health related and general Quality of Life (QOL) in elderly. Methods: Subjects were 612 community dwelling Thai aged 60 years or older. A questionnaire was evaluate socio-demographics, general oral health assessment index (GOHAI) and world health organization quality of life (WHOQOL). Oral examinations assessed teeth present, decayed teeth, gingival bleeding, pocket depth, functional tooth units (FTUs) and salivary flow rate. Results: For dentate subjects (n=428), logistic regression showed that teeth present, decayed teeth, gingival bleeding, pocket depth, FTUs and saliva flow rate were associated with GOHAI (p < 0.05). Regarding WHOQOL, teeth present, gingival bleeding and FTUs were associated with physical domain (p < 0.05). Teeth present, decayed teeth, gingival bleeding and FTUs were related with psychological domain (p<0.05). Teeth present and FTUs were associated with environmental and social domain (p < 0.05). For edentulous subjects (n=184), denture wearing was associated with GOHAI and all domains of WHOQOL (p < 0.05). Conclusion: The number of teeth present, denture wearing and FTUs strongly affected GOHAI and general QOL. Dental caries, periodontal status and salivary flow rate also affected GOHAI and some domains of general QOL of elderly.